Pengaruh Social Media Addiction terhadap Depresi dengan Social Comparison Sebagai Variabel Moderator pada Pengguna Instagram - Onggono, Jessica Noviana; Virlia, Stefani (Psychopreneur Journal, 2021)
The purpose of this study is to determine whether social comparison can moderate the influence between social media addiction to depression in Instagram user. Hypotesis of this study is social comparison can moderate the influence of social media addiction toward depression in Instagram users. This study is a quantitative research and data are collected using depression scale “Beck Depression Inventory Second Edition”, social media modified scale “Bergen Facebook Addiction Scale”, and social comparison scale “Iowa-Netherlands Comparison Orientation Measure”. The scales were spread across 98 subjects. The result show that social comparison can not moderate the influence of social media addiction towards depression (R2 = 0.045; p = 0.912; p > 0.05), because social comparison are not always negative, so social comparison did not strengthen or weaken the influence of social media addiction toward depression in Instagram users